2023
DOI: 10.1186/s12866-023-02802-3
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis plasmid-encoding Pgp3 protein induces secretion of distinct inflammatory signatures from HeLa cervical epithelial cells

Abstract: Background Genital Chlamydia trachomatis infection is the most common bacterial sexual transmitted disease that causes severe complications including pelvic inflammatory disease, ectopic pregnancy, and infertility in females. The Pgp3 protein encoded by C. trachomatis plasmid has been speculated to be an important player in chlamydial pathogenesis. However, the precise function of this protein is unknown and thus remains to be thoroughly investigated. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Chemokines belonging to the C-X-C family are known to play a role in leukocyte recruitment and regulate the tumor microenvironment by controlling tumor cell proliferation, metastasis, invasion, angiogenesis, and therapeutic resistance [ 23 ]. Numerous studies on Chlamydia trachomatis have demonstrated its capacity to upregulate C-X-C chemokine levels at the site of infection, thereby inducing an intense inflammatory response [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines belonging to the C-X-C family are known to play a role in leukocyte recruitment and regulate the tumor microenvironment by controlling tumor cell proliferation, metastasis, invasion, angiogenesis, and therapeutic resistance [ 23 ]. Numerous studies on Chlamydia trachomatis have demonstrated its capacity to upregulate C-X-C chemokine levels at the site of infection, thereby inducing an intense inflammatory response [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purified Pgp3 protein stimulates macrophages to release inflammatory cytokines (Li et al, 2008 ). It induces the expression of a series of host inflammatory cytokine genes, including interleukin-6 (IL-6), IL-8, tumor necrosis factor alpha-induced protein 3 (TNFAIP3), and chemokine C-X-C motif ligand 1 (CXCL1), after stimulating HeLa cells (Cheong et al, 2023 ). The involvement of tumor necrosis factor receptor 1 (TNFR1) in Chlamydia pathogenesis is supported by crystal analyses that have shown that the Pgp3 C-terminal trimerization domain resembles the TNF-like domain (Galaleldeen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of C. trachomatis proteins with host proteins involves altering vesicular transport in extracellular vesicles, regulating cell survival pathways, and suppressing the innate host immune response. The Chlamydial effector proteins interfere with the host’s innate immune response, such as INCs, TepP ( 35 ), CPAF, Pgp3 ( 36 ), Pgp4 ( 37 ) and 60 other proteins ( 38 ), which promote intracellular survival of Chlamydia and limit the host response to infection. RBs continue to differentiate in inclusions and, at later stages, asynchronously undergo secondary differentiation to create new EBs.…”
Section: Pathogenesis and Immunitymentioning
confidence: 99%